The signal in the noise - Florian Berg; Jason Jay; Julian Kölbel; Roberto Rigobón (EconPol Forum, 2023)
The information that ESG raters produce is valuable. Assessing ESG performance is conceptually challenging because we need to measure contextuality, additionality, and preferences. ESG raters, specialized ESG data providers, and aggregators can harness economies of scale. Regulators should enforce transparency of measurement and aggregation practices to increase competition between ESG raters to incentivize improvement
Keywords: 330